2018
DOI: 10.1371/journal.ppat.1007117
|View full text |Cite
|
Sign up to set email alerts
|

Murine leukemia virus p12 tethers the capsid-containing pre-integration complex to chromatin by binding directly to host nucleosomes in mitosis

Abstract: The murine leukaemia virus (MLV) Gag cleavage product, p12, is essential for both early and late steps in viral replication. The N-terminal domain of p12 binds directly to capsid (CA) and stabilises the mature viral core, whereas defects in the C-terminal domain (CTD) of p12 can be rescued by addition of heterologous chromatin binding sequences (CBSs). We and others hypothesised that p12 tethers the pre-integration complex (PIC) to host chromatin ready for integration. Using confocal microscopy, we have observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…We therefore think it likely that some sort of uncoating event begins at the nuclear pore and finishes at the site of integration. We have also previously shown that the murine leukaemia virus (MLV) p12 protein binds directly to both CA and nucleosomes, tethering the MLV core to chromatin during mitosis, and have proposed that p12 could be acting in a similar capacity to CPSF6 in HIV-1 infection [ 87 ]. Fig 9 includes our model of MLV uncoating.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore think it likely that some sort of uncoating event begins at the nuclear pore and finishes at the site of integration. We have also previously shown that the murine leukaemia virus (MLV) p12 protein binds directly to both CA and nucleosomes, tethering the MLV core to chromatin during mitosis, and have proposed that p12 could be acting in a similar capacity to CPSF6 in HIV-1 infection [ 87 ]. Fig 9 includes our model of MLV uncoating.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] The murine leukemia virus (MLV) GAG p12 fragment interaction with mitotic chromatin has also been characterized. [ 36 ] Chromatin binding by MLV‐p12 and PFV‐CBS appear mutually exclusive, as their binding sites are the same. The structure of the tetrameric PFV intasome bound to nucleosome reveals how the viral DNA gets integrated into host chromatin.…”
Section: Nucleosome Acidic Patch: a Docking Station For Viral Proteinmentioning
confidence: 99%
“…We therefore think it likely that some sort of uncoating event begins at the nuclear pore and finishes at the site of integration. We have also previously shown that the murine leukaemia virus (MLV) p12 protein binds directly to both CA and nucleosomes, tethering the MLV core to chromatin during mitosis, and have proposed that p12 could be acting in a similar capacity to CPSF6 in HIV-1 infection [84]. Figure 9 includes our model of MLV uncoating.…”
Section: Discussionmentioning
confidence: 98%